2022
DOI: 10.1128/mbio.00518-22
|View full text |Cite
|
Sign up to set email alerts
|

Candida auris on Apples: Diversity and Clinical Significance

Abstract: In 2019, the U.S. Centers for Disease Control and Prevention classified the multidrug-resistant Candida auris as one of five pathogens posing the most urgent threats to public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…These environmental strains were genetically close to the clinical isolates from India (South Asian clade) and, with the exception of one isolate, showed multidrug resistance [ 37 ]. Moreover, C. auris was isolated from the surfaces of stored apples; these strains were closely related to strains from patients, hospitals in India as well as to clinical strains from other parts of the world (South Asian clade) [ 38 ]. As hospital environmental isolates may be the source of colonization or infection in critically ill patients, antifungal susceptibility testing of these isolates is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…These environmental strains were genetically close to the clinical isolates from India (South Asian clade) and, with the exception of one isolate, showed multidrug resistance [ 37 ]. Moreover, C. auris was isolated from the surfaces of stored apples; these strains were closely related to strains from patients, hospitals in India as well as to clinical strains from other parts of the world (South Asian clade) [ 38 ]. As hospital environmental isolates may be the source of colonization or infection in critically ill patients, antifungal susceptibility testing of these isolates is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Tracking the geographical origin and the dynamics of spread is especially challenging in fungi due to their complex ecology and the large timescales, usually, millennia, that encompass the evolution of these organisms [4,36]. Reconstructing likely scenarios for spread is essential to understanding disease emergence and risks to public health; both natural history and human commercial activities have been correlated with the emergence of fungal etiologic agents and fungal resistance, such as in Candida auris [37,38] and C. gattii VGII [39]. These advances/theories are particularly reliant on whole-genome sequencing and molecular clock analyses that reveal the time scale and patterns of evolution; these efforts are ongoing for C. gattii VGVI.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Yadav et al ( 1 ), the investigators screened fruits for the presence of fungi and identified a large number of fungal species present on the surfaces of fruit. A total of 84 fruits from 9 different plant species were screened from northern India, and a total of 144 yeast strains were isolated, including pathogenic and nonpathogenic species.…”
Section: Commentarymentioning
confidence: 99%
“…Apart from the isolated fungi, the investigators also detected antifungal compounds on the surface of stored apples as well as on freshly picked apples from nonorganic orchards ( 1 ). This is not surprising because antifungals are commonly employed during storage to extend the life of fruit and during cultivation to reduce the risks of infection.…”
Section: Commentarymentioning
confidence: 99%